2002
DOI: 10.1590/s0103-50532002000600014
|View full text |Cite
|
Sign up to set email alerts
|

Local intersection volume (LIV) descriptors: 3D-QSAR models for PGI2 receptor ligands

Abstract: Prostaciclina I 2 inibe a agregação plaquetária pela interação com um receptor específico de membrana. Neste trabalho, desenvolvemos modelos de QSAR-3D para uma série de compostos heterocíclicos aromáticos usando como descritor o volume de interseção local. Os modelos obtidos podem ser aplicados no desenvolvimento de novos ligantes de receptor da PGI 2 com potencial atividade anti-agregante plaquetária.Prostacyclin I 2 inhibits platelet aggregation through specific binding to its membrane receptor. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Thus further substitution at atom C 6 can decrease the inhibitory activity. Local Intersection Volume (LIV) [46,47], a 3D local shape descriptor, is used for QSAR study of arylbenzothiophene-raloxifene analog for inhibitory activity as a case study. The model [13] (n = 41; R 2 = 0.76; Q 2 = 0.68) also supports the importance of 7-hydroxyl group, ether linkage and piperidine ring for the activity.…”
Section: Qsar Studiesmentioning
confidence: 99%
“…Thus further substitution at atom C 6 can decrease the inhibitory activity. Local Intersection Volume (LIV) [46,47], a 3D local shape descriptor, is used for QSAR study of arylbenzothiophene-raloxifene analog for inhibitory activity as a case study. The model [13] (n = 41; R 2 = 0.76; Q 2 = 0.68) also supports the importance of 7-hydroxyl group, ether linkage and piperidine ring for the activity.…”
Section: Qsar Studiesmentioning
confidence: 99%
“…GFA applies the same procedures described above for GAs, and coupled with PLS, the GFA-PLS technique has as its most important feature the generation of multiple good models rather than the optimization of only a single model [ 53 ]. Several authors have reported the use of combined GA and PLS analyses [ 28 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%